Resepsi Al-Quran Di Pondok Pesantren Al-Hidayah Karangsuci Purwokerto - akhmad roja badrus zaman (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
The Qur'an is truly a holy book containing moral teachings to guide people to the straight path. It's just that, when the Qur'an is consumed by the public, the book experiences a paradigm shift so that it is treated, received, and expressed differently according to their respective knowledge and beliefs. That expression, of course, is a concrete indicator that the Qur'an is a holy book which is always in harmony with all situations and conditions (á¹£Älih li kulli zamÄn wa makÄn). The model and style of the reception even now continue to be expressed and preserved by the family of Ponpes Al-Hidayah Karangsuci, Purwokerto. This study aims to determine the variety of Al-Qur'an receptions in Ponpes and try to understand the meaning inherent in it. This research was designed with qualitative methods and included in field research. In obtaining data, the instruments that researchers use are in-depth interviews, observations, and studies of related documents. The analysis used by researchers is as presented by Mohd. Soehadha, namely by reducing data, displaying data, and drawing conclusions. In clarifying the validity of the data, the researcher extends the participation and triangulation of sources and methods. From the research conducted, the results obtained include: (1) a variety of Al-Qur'an receptions in the Al-Hidayah Islamic Boarding School Karangsuci Purwokerto, (2) The meanings inherent in the reception variety, among others: objective meaning, expressive meaning, and documentary meaning. The objective meaning is to conclude that the variety of reception behavior at the Islamic boarding school is a symbol of compliance and injustice to the regulations of the boarding school. The expressive meaning is a form of self-internalization with positive things through the continuous learning process of the Qur'an, and the meaning of the documentary is a form of local contextualization of the whole cultural system.